ANALISIS ANGKATAN KERJA, DAN TENAGA KERJA TERHADAP TINGKAT PENGANGGURAN SMA SEDERAJAT DI PROVINSI BANGKA BELITUNG - Erwandy; Buulolo, Martinus (Jurnal Ilmiah Niaga Bisnis Elektronik, 2024)
Unemployment is an important issue in the economy, especially in Bangka Belitung Province which faces challenges in absorbing high school graduates into the job market. This analysis aims to evaluate the influence of the workforce and labor force on the unemployment rate in the area. This study uses secondary data analyzed using the multiple regression method through SPSS software. The variables analyzed include the workforce and labor force as independent variables, with the unemployment rate as the dependent variable. The t-test is used to test the significance of the influence of each independent variable, while the F-test is used to evaluate the overall significance of the regression model. The determination test (R²) is applied to assess how much of the variation in the unemployment rate can be explained by the model. The results of the t-test indicate that the workforce and labor force each have a significant influence on the unemployment rate. A positive coefficient for the workforce indicates that an increase in the workforce is associated with an increase in the unemployment rate, while a coefficient for the labor force indicates that an increase in the labor force is associated with a decrease in the unemployment rate. The F-test shows that the multiple regression model as a whole is significant in explaining the variation in the unemployment rate. The R² value indicates that this model can explain most of the variation in the unemployment rate